Late-Onset Rejection in Liver Allograft Biopsies: An Analysis of Process, Pattern, and Clinical Implications. Issue 3 (20th February 2023) - Bateman, Justin; Anugwom, Chimaobi; Zhou, Yan; Lim, Nicholas; Adeyi, Oyedele
Abstract: Objectives: Both alloimmune and nonalloimmune factors affect the long-term survival of liver allograft recipients. Various patterns of late-onset rejection are recognized, including typical acute cellular rejection (tACR), ductopenic rejection (DuR), nonspecific hepatitis (NSH), isolated central perivenulitis (ICP), and plasma cell–rich rejection (PCRR). This study compares the clinicopathologic features of late-onset rejection (LOR) in a large-cohort context. Methods: For-cause liver biopsies more than 6 months after transplant were included from the University of Minnesota between 2014 and 2019. Histopathologic, clinical, laboratory, treatment, and other data were analyzed in nonalloimmune and LOR cases. Results: The study consisted of 160 patients (122 adults, 38 pediatric patients), with 233 (53%) biopsies showing LOR: 51 (22%) tACR; 24 (10%) DuR; 23 (10%) NSH; 19 (8%) PCRR; and 3 (1%) ICP. Mean onset of 80 vs 61 months was longer for nonalloimmune injury ( P = .04), a difference lost without tACR (mean, 26 months). Graft failure was highest with DuR. Response to treatment, as measured by changes in liver function tests, was similar between tACR and other LORs, and NSH occurred more often in pediatric patients ( P = .001); tACR and other LOR incidence was similar. Conclusions: LORs occur in pediatric and adult patients. Except for tACR, patterns overlap in many ways, with DuR having the greatest risk of graft loss, but other LORs respond well to antirejection treatments.